CENTERING VULNERABLE INTERESTS: THE CONSTRUCTION OF WOMENâS PROTECTION MODEL FROM FIELD LESSONS - Hendrastiti, Titiek Kartika; Riza, Irna (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
The position of women in Indonesian society is progressing. The progress trend is supported by several legal instrumentsÂ and policies that guarantee womens rights. Although adequate legal instruments began, many implementations in theÂ field are distorted. Implementation of the protection schemes for women does not address to the changing of the poorÂ womenâs living condition, instead it remains vulnerable. This action research was addressed to analyze and discussÂ the practices of state social protection for the poor communities, as well as the testimony of beneficiaries. Based on theÂ field learning from both parties, activists from universities and non-governmental organizations, attempt was made toÂ knit some state schemes and policies into a model of protection; it also aimed to facilitate access and accelerateÂ changes.